Formulation of Gel Peel-Off Salt Mask with a Combination Sargassum duplicatum Extract Against Propionibacterium acnes - Halimatus Sa'diyah; Subekti, Sri; Amin Alamsjah, Mochammad (Journal of Marine and Coastal Science, 2025)
Acne is a facial skin problem that can be caused by a Propionibacterium acnes infection. A peel-off gel mask is a cosmetic product that is usually used to treat facial skin problems. Peel-off gel masks can be formulated with a mixture of natural ingredients such as salt and seaweed. Sargassum duplicatum is a type of brown seaweed that is rich in bioactive compounds such as flavonoids, terpenoids, and saponins, which can support skin beauty. The combination of salt and S. duplicatum extract can be formulated in the form of a peel-off gel mask to meet pharmaceutical requirements. The aim of this research is to determine the effect of salt concentration in each treatment and to determine the optimum salt concentration that can inhibit P. acnes in peel-off gel mask preparations with a combination of S. duplicatum extract. This research used a Completely Randomised Design (CRD) consisting of four treatments. The treatments consisted of different salt concentrations of 0%, 10%, 15%, and 20%. The parameters in this research are antibacterial effectiveness, organoleptics, and pH. Research data was analysed using Analysis of Variance (ANOVA). The research results showed that the use of salt in the peel-off gel mask formulation had an effect on the inhibition zone against P. acnes, the panellists' organoleptic acceptability, and the pH value. The antibacterial activity test showed that there was inhibitory power against P. acnes bacteria in salt concentration of 20% and an inhibition zone of 13.5 mm. The organoleptic test results showed good acceptance from the panellists for each treatment. The pH test results showed that all treatments met SNI 16-4399-1966 with an average pH value of 5.8 - 6.6.